The level of inclusion of twenty-first-century skills in the mathematics textbook for the second grade of secondary school in the Kingdom of Saudi Arabia - Almohammadi, Iman Saed (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to identify the availability of 21st century skills in the mathematics book second grade secondary from the point of view of teachers, and to know the statistical differences between teachers and teachers about the availability of 21st century skills in the second grade mathematics book, different variable (scientific qualification, years of experience). The researcher used the descriptive survey method, and a simple random sample was selected from the study community, and the study sample consisted of (89) teachers and mathematics teachers for the secondary level and the questionnaire was used as a tool to measure, and the study tool was formed (45). Paragraph divided into four axes: skills of creativity, innovation, dialogue and communication skills, culture skills in the digital age, skills of profession and life, One of the most important results of the research was the following: the degree of availability of 21st century skills in the book of mathematics second grade secondary came with an average degree, the lack of statistically significant differences at the level of 0.05 and less between the answers of teachers and teachers about the availability of 21st century skills in the book of mathematics second grade secondary due to the variable years of experience, The existence of statistically significant differences at the level of 0.05 and lower between the answers of teachers about the availability of 21st century skills in the second-grade mathematics book secondary due to the variable qualification in favor of the Doctor
Keywords: Range; 21st century skills; math teachers